Engagement of the Serbian Army in helping civilians in the event of nuclear and chemical accidents - Inđić, Dejan R.; Terzić, Miroslav R.; Žigić, Stevan V.; Rutić, Srđan Z. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Nuclear and chemical accidents in modern society often cause devastating consequences to people, material resources and the environment. This kind of accident requires special procedures and activities during the elimination of the consequences, because of the specific characteristics of highly toxic substances used in nuclear and chemical plants. The Serbian Army with its units and organizations can contribute significantly to the implementation of tasks of eliminating the consequences of such accidents. The paper describes the role and the tasks of the Serbian Army as well as one of the methods to utilize its units to provide assistance to the population in case of nuclear and chemical accidents. Introduction Today, for peacetime applications, many different sources of radiation are used, among which nuclear reactors are certainly the most dangerous. Due to accidents that occurred in the previous period, the risk of nuclear accidents is not negligible, and potential consequences are usually disastrous. Accidents at chemical complexes and uncontrolled releases of hazardous substances into the environment are much more likely to happen. Accidents at such plants throughout the world are very common, and the resulting effects on people, property and the environment are often significant. The elimination of consequences occurring atnuclear sites or by chemical accidents engages all structures of the society, in accordance with the duties and assigned tasks, including a significant role of the units and institutions of the Serbian Army. Tasks, resources and forces of the Serbian Army to assist the population in nuclear and chemical accidents The tasks of the Army of Serbia arise from doctrinal documents on its use within assigned missions. Assisting the population in NC accidents is defined in the 3rd mission of the Army: "Support to civilian authorities in countering threats to security," and the central task within it is to assist civilian authorities in responding to natural, technological and other disasters. The Army of Serbia has no special forces intended for the implementation of these tasks, but it engages the existing ones depending on the extent of accident consequences. Also, when providing assistance to civilian authorities, the NC accident units of the Serbian Army use their equipment and, if necessary, supplement it with local and handy tools that can be used for this purpose. Display of the engagement of the Serbian Army to provide assistance to the population in case of nuclear or chemical accidents To assess the modeling power of the Army of Serbia to participate in the elimination of accident consequences, we first perform the modeling of accidental situations and budget resulting consequences.The probability of nuclear accidents in the territory of the Republic of Serbia is low, so chemical accidents have been modellled with their possible consequences as well as the forces of Serbia which can be used effectively with other entities of the society to solve the resulting problems. Engaging the SA units in eliminating the consequences of NC accidents would consist of several main tasks, namely: – Providing emergency care for injured and intoxicated – authorities realize the medical service by forming temporary clinics; – Removing obstacles and debris – mostly by engaging engineering units with their machinery, but for more considerable damage, armored and mechanised units, or infantry units may be included. – Fire fighting – firefighting units trained for these tasks assist police; – Radiological and chemical reconnaissance – RBC survey service units are primarily engaged , but at higher concentrations of radioactivity and hazardous substances, armored mechanised units and aviation can also provide assistance; – Radiological and chemical decontamination – RBC service decontamination units are primarily engaged , and, if necessary, engineering units, river flotilla and logistics services can be included; – Evacuation of civilians – in accordance with the situation, all SA transport capacity can be engaged: transportation service units, aviation transport units, river flotilla, etc. Conclusion For an optimum response to the occurrence of nuclear or chemical accidents and in accordance with prescribed procedures, there is a need for trained and equipped forces of the State, which would be engaged in eliminating NC accident consequences. Successful and coordinated work on eliminating the consequences involves continuous training of units to operate in these conditions. This problem can be solved by the implementation of joint exercises of all forces involved in the integrated response to accidents ( businesses, local authorities, medical teams, the forces of the Ministry of Interior and the Ministry of Defence, etc.). Units and institutions of the Serbian Armed Forces can take an active part in the elimination of the consequences of NC accidents only if they are fully trained and equipped for the implementation of assigned tasks.